2016
DOI: 10.3892/or.2016.5323
|View full text |Cite
|
Sign up to set email alerts
|

High concordance rate of KRAS/BRAF mutations and MSI-H between primary colorectal cancer and corresponding metastases

Abstract: Genetic testing is needed for the treatment of colorectal cancer (CRC), especially molecular-targeted therapy. The effects of anti-EGFR therapy and prognosis are affected by the presence of KRAS mutations. However, whether primary CRC or metastatic tissues are appropriate in the analysis is still unclear. In the present study, we assessed the concordance of KRAS/BRAF mutation status and microsatellite instability (MSI) in primary CRC and corresponding metastases. This study enrolled 457 patients with surgicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 40 publications
5
68
1
1
Order By: Relevance
“…Also, among the few patients with mutation heterogeneity, the temporal nature of the disease had no effect, in line with the findings from previous studies. [43][44][45] Nevertheless, heterogeneity in CRC beyond driver gene mutations has been demonstrated and is likely to affect tumor progression and the response to treatment. A large number of subclones in the primary tumor, which correlated with a high degree of heterogeneity, 46 and the heterogeneity of genome-wide copy number aberrations 18 have both been associated with a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Also, among the few patients with mutation heterogeneity, the temporal nature of the disease had no effect, in line with the findings from previous studies. [43][44][45] Nevertheless, heterogeneity in CRC beyond driver gene mutations has been demonstrated and is likely to affect tumor progression and the response to treatment. A large number of subclones in the primary tumor, which correlated with a high degree of heterogeneity, 46 and the heterogeneity of genome-wide copy number aberrations 18 have both been associated with a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Change in MSI status is important because studies have shown that only patients with deficient MMR (dMMR) or MSI-high tumors benefit from anti-PD-1 therapy. 17,18 Haraldsdottir et al 19 reported a 100% concordance rate in MMR status between the primary tumor and corresponding metastatic tissue in 25 patients with CRC, whereas Fujiyoshi et al 20 found a discordance in 3 patients and Jung et al 21 found a concordance rate of only 77%.…”
Section: Introductionmentioning
confidence: 99%
“…It is desirable that all‐ RAS analysis is performed early in the surgical management of CLM patients. Because the all‐ RAS mutation status of the primary tumor and CLM usually showed >95% concordance, endoscopic biopsy, or surgical specimens of primary tumor can be confidently used for the all‐ RAS mutation analysis to predict the prognosis and for clinical decision‐making in relation to anti‐EGFR antibody therapy before hepatic resection in CLM patients …”
Section: Discussionmentioning
confidence: 99%
“…| 753 prognosis and for clinical decision-making in relation to anti-EGFR antibody therapy before hepatic resection in CLM patients. 25,[43][44][45]…”
Section: Discussionmentioning
confidence: 99%